Perancangan Aplikasi Android Untuk Media Pembelajaran Budidaya Tanaman Secara Hidroponik Dengan Metode Demon-Disco Learning - Daniel Novianto (STEKOM PRESS, 2018)
Utilization of a mobile device with the Android operating system that is used as a supporting medium and supplement in improving learning outcomes combined with demonstration and discovery learning or demon-disco learning methods is needed to help students improve learning outcomes in vocational competence subjects in hydroponic crop cultivation in vocational high schools Kristen Terang Bangsa, because the use of android-based applications can provide new experiences regarding the use of information and communication technology, as well as provide opportunities for students to be able to learn more independently. The concept chosen as a learning media is to explain the material about understanding, introduction of parts, types, and quiz containing questions about hydroponic plant cultivation. This research uses the Research and Development (RnD) product development method, using 6 out of 10 stages research that is the potential and problems, data collection, product design, design validation, design improvement, product trials. The results of this study are to produce learning media in the form of Android-based applications. The validity value of media experts is 2.6 which is declared feasible, while the validity value of material experts is 3.6 which is declared feasible, and is able to increase the average value in the subject of vocational competence in hydroponic cultivation in Christian Terang Bangsa Vocational Schools which initially 67 (with 13 students who had not yet reached KKM) to 80 (with 4 students who had not yet reached KKM).